Performance management systems : an experiential approach - Varma, Arup; Budhwar, Pawan S. (Thousand Oaks : SAGE Publications Ltd., 2020)
An experiential and skills-building approach, exploring the realities and complexities of performance management and encouraging a reflective, adaptable outlook and equipping readers to conduct performance management in the future. The book presents the theoretical underpinnings and the practical applications of key topics in detail, with practical concepts or skills highlighted in terms of how they fit into the Performance Management system. Learning features include: "Developing PMS Skills" boxes, highlighting a particular skill "PMS in Practice" boxes, showcasing real-life examples from around the world "Experiential Exercises", to encourage active learning A comprehensive suite of free online resources, including PowerPoint Slides, full journal articles, and self-review questions an be found at https://study.sagepub.com/varma Suitable for Performance Management modules on Human Resource Management, General Management and Organisational Behaviour courses.
Includes bibliographical references.
Keywords: elektronické knihy; electronic books; Business and Management -- Performance Management -- Organizational Performance Management